Scarcity Marketing dan Arousal terhadap Impulse Buying Live Streaming Tiktok Shop - Dina Wardatul Maula; Hanafi Adi Putranto (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to analyze the effect of scarcity marketing on impulse buying through arousal as a mediating variable among TikTok Shop users in Indonesia. The live shopping phenomenon on the TikTok Shop platform has created unique consumer behavior dynamics, where product scarcity strategies become the main trigger for impulsive purchases. This study employs a quantitative approach with a survey method involving 250 respondents who are TikTok Shop users who have made purchases through the live streaming feature. Data analysis techniques using Structural Equation Modeling (SEM) were applied to examine the relationships between variables. The results show that scarcity marketing has a positive and significant effect on arousal (β=0.742; p<0.001) and impulse buying (β=0.389; p<0.001). Arousal is also proven to have a positive and significant effect on impulse buying (β=0.456; p<0.001) and mediates the relationship between scarcity marketing and impulse buying (indirect effect=0.338; p<0.001). These findings confirm that time and quantity scarcity strategies can stimulate consumers' emotional arousal, which subsequently drives spontaneous purchase decisions. This study provides theoretical contributions in understanding the psychological mechanisms of digital consumers and practical implications for business practitioners in designing effective live commerce marketing strategies.